Working donkey welfare assessment and owner survey in Meru County, Kenya - Martha Mellish; Jason Stull (Animal Welfare)
There are significant welfare concerns regarding the plight of working donkeys (Equus asinus) in developing countries. To-date, however, there has been limited work assessing the welfare of donkeys in many parts of Africa, including Kenya. This study aimed to characterise the unique welfare concerns of working donkeys in Meru County, Kenya. Baseline information was gathered, concerning challenges with feeding, working conditions and disease faced by owners and drivers with differences between pack and cart donkeys investigated. To this end, 102 donkeys underwent evaluation using a Standardised Equine Based Welfare Assessment Tool (SEBWAT) and 58 owners were surveyed. Important welfare concerns, including low body condition scores (BCS) (median [IQR] 2 [1.5, 2.5 out of 5]), hobbling (81/102; 79%) and mutilation wounds (49/102; 48%) were identified in all donkeys. The following categories registered significant physical differences between cart and pack donkeys: signalment (cart 100% male, pack 21% male); BCS (median cart 2.0, pack 1.5); and presence of skin wounds on the neck (cart 30%, pack 0%). Behaviour was assessed with differences noted in chin contact avoidance (cart 56%, pack 97%), tail tuck presence (cart 46%, pack 97%), number of donkeys owned (median cart 2, pack 1), reported administration of de-worming medication by owners (cart 95%, pack 17%), and occurrence of reported illness (cart 81%, pack 38%). This initial survey addresses welfare concerns related to the Meru County donkey population and will serve as a useful benchmark for future assessments as well as targeted interventions, including the introduction of modified carts to the region.